2018
DOI: 10.1371/journal.pone.0193333
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of PCNA mutant proteins defective in gene silencing suggest a novel interaction site on the front face of the PCNA ring

Abstract: Proliferating cell nuclear antigen (PCNA), a homotrimeric protein, is the eukaryotic sliding clamp that functions as a processivity factor for polymerases during DNA replication. Chromatin association factor 1 (CAF-1) is a heterotrimeric histone chaperone protein that is required for coupling chromatin assembly with DNA replication in eukaryotes. CAF-1 association with replicating DNA, and the targeting of newly synthesized histones to sites of DNA replication and repair requires its interaction with PCNA. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…Pcna-6 shows a minor defect in cell growth, but a high sensitivity to hydroxyurea (24). The crystal structures of PCNA (44) and the pcna-6 mutant (45) are shown in Figure 4B. The main distinguishing characteristics are decreased hydrophilicity on the surface side that binds Pol δ (23,46–48).…”
Section: Resultsmentioning
confidence: 99%
“…Pcna-6 shows a minor defect in cell growth, but a high sensitivity to hydroxyurea (24). The crystal structures of PCNA (44) and the pcna-6 mutant (45) are shown in Figure 4B. The main distinguishing characteristics are decreased hydrophilicity on the surface side that binds Pol δ (23,46–48).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that this weak binding to PCNA by CAF-1 may promote nucleosome assembly without disrupting normal DNA replication events [106]. The results from a structural analysis of PCNA mutant proteins with defective gene silencing showed that the mutation sites were all located in a cavity at a distance from canonical binding sites, indicating a second binding mode for the CAF-1-PCNA interaction [107]. PCNA can recruit CAF-1, while CAF-1 itself shows DNA-binding activity.…”
Section: Pcna: Marking the Replication Fork For Caf-1-mediated Nucleomentioning
confidence: 99%
“…Additionally, many DNA repair factors contain PCNA-Interacting Protein (PIP) or PIP-like motifs (reviewed in Boehm and Washington (2016)). The pol30-6 and pol30-79 mutations disrupt the cleft of PCNA that bind PIP motifs (Kondratick et al 2018), which could prevent the recruitment of DNA repair factors to sites of DNA damage. These results could explain the high levels of DNA damage and mitotic recombination in pol30-6 and pol30-79.…”
Section: A Surprising Effect Of Ploidy On Silencing Instabilitymentioning
confidence: 99%